Case report: Non‐invasive neurally adjusted ventilatory assist in a newborn with unilateral diaphragmatic paralysis. Issue 11 (19th April 2016) - Roosens, Sander; Derriks, Frank; Cools, Filip
Summary: Diaphragmatic paralysis is a rare cause of respiratory distress in the newborn. In this paper, a patient with unilateral phrenic nerve injury after traumatic delivery is presented. The child inadequately responded to standard respiratory supportive measures. Non‐invasive neurally adjusted ventilatory assist (NIV‐NAVA®), providing an optimally synchronized respiratory support proportional to the effort of the patient, resulted in prompt clinical and biological improvement of the patient's respiratory condition. NAVA is a relatively new mode of ventilation in neonatal care. In this case of unilateral diaphragmatic paralysis, it provided an alternative strategy of non‐invasive respiratory support avoiding prolonged mechanical ventilation.Pediatr Pulmonol. 2016;51:E37–E39. © 2016 Wiley Periodicals, Inc.